Pengaruh Safety Climate dan Perceived Supervisor Safety terhadap Safety Performance yang Dimediasi oleh Psychological Strain: Studi pada PT PAL Indonesia (Persero) - Dito Vidya Riadianto; Ahmad Rizki Sridadi (Universitas Proklamasi 45, 2021)
The role of human research is basic to determine the objective of an organization or company. The case of a work accident can be detrimental for workers and can decrease the safety performance of the company. Some factors could affect it for instance human factors (unsafe actions), which are caused by undiscipline in applying regulation of work, worker's skilled less in mastering production tools, etc. While environmental factors can be caused by various things for instance an unsafe circumstance of work which concerns all equipment or machinery, and also buildings. The purpose of this research is to obtain the knowledge to gain broader knowledge about the influence of Safety Climate, Perceived Supervisor Safety, and Psychological Strain on Safety Performance. The research population is about 115 employees consist of 45 supervisors and 70 active employees in the Commercial Ship Division of PT PAL Indonesia (Persero), Surabaya. Due to a total population of 115 employees which consist of 45 supervisors, and 70 active employees are used as respondents to the commercial ship division. The data analysis in this research uses partial least square (PLS). The result obtained from this research is that safety climate and perceived supervisor safety are low practice, so the company's safety performance will be low as well and for the psychological strain highly level could make a negative impact on the company's safety performance.